Assessment of Crime Incidence and Mitigation Strategies in Selected Indigenous Markets in Ibadan - Abayomi, OLADELE Joshua (2019)
The study examined the perceived incidence, causes and effects of crime within and around two selected indigenous markets in Ibadan. The primary data used in the study were sourced from traders, buyers and neighbouring residents through the use of questionnaire survey. Systematic and accidental samplings were used to select a total of 224 respondents. Four indices were developed: ‘Incidence of Crime Index’ (ICI), ‘Causes of Crime Index’ (CCI), ‘Effects of Crime Index’ (ECI) and ‘Security Measures Index’ (SMI). ICI, CCI, ECI and SMI were used to measure the incidence, causes and effects of crime as well as the security measures employed against crime in the selected markets and their neighbourhoods. The study observed that theft/ pick pocketing (4.54) and receiving stolen goods (4.47) were among the most prominent crime incidences. Poverty (CCI= 4.34) and lack of education (CCI= 4.34) are the highly perceived causes of crime in the study area. Loss of properties (ECI= 4.55) ranked highest in the respondents’ perceived effect(s) of crime in the study area while loss of lives, fear of being the next victim and mental disorder also ranked high with ECI values = 4.13, 4.12 and 4.01 respectively. Special windows and doors lock had the highest usage index (SMI= 3.91) while burglary proofing materials, security guards, vigilante, police, access road/ transport means and traditional means i.e. juju were similarly rated high with SMI values of 3.86, 3.85, 3.73, 3.51, 3.07 and 3.03 respectively. The study concluded that crime incidence in the area was serious and the residents were skeptical about police protection. However, it is suggested that relevant security agencies in the areas should adopt a proactive approach to crime prevention. This is premised on the fact that necessary and effective mechanisms for crime prevention are means of issuing strong deterrent signals to crime perpetrators and gives safety assurance to members of the society. Keywords: Crime, Indigenous market, Mitigation, Strategies DOI: 10.7176/JLPG/89-19 Publication date:September 30th 201